2015
DOI: 10.1039/c4ra15498c
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles supported on silica-coated ferrite as magnetic and reusable catalysts for oxidant-free alcohol dehydrogenation

Abstract: The oxidant-free dehydrogenation of alcohols to corresponding carbonyl compounds has been performed by using silver (0) nanoparticles supported on silica-coated ferrite as an efficient and recyclable heterogeneous catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
(28 reference statements)
0
32
0
Order By: Relevance
“…Du 33 Kooti et al have successfully synthesized the CoFe 2 O 4 /SiO 2 /Ag composite through a three-step procedure for using as an antibacterial agent of both Gram-positive and Gram-negative bacteria. Du 33 Kooti et al have successfully synthesized the CoFe 2 O 4 /SiO 2 /Ag composite through a three-step procedure for using as an antibacterial agent of both Gram-positive and Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Du 33 Kooti et al have successfully synthesized the CoFe 2 O 4 /SiO 2 /Ag composite through a three-step procedure for using as an antibacterial agent of both Gram-positive and Gram-negative bacteria. Du 33 Kooti et al have successfully synthesized the CoFe 2 O 4 /SiO 2 /Ag composite through a three-step procedure for using as an antibacterial agent of both Gram-positive and Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…However, the designing of highly recyclable heterogeneous systems still remains a significant challenge for oxidant‐free dehydrogenation of alcohols. Our research group has previously reported silver nanoparticles supported on silica‐coated magnetic nanoparticles (Fe 3 O 4 @SiO 2 ‐Ag) as a heterogeneous catalyst for oxidant‐free alcohol dehydrogenation . Our results indicated that the reaction time was very long for oxidant‐free dehydrogenation of alcohols using Fe 3 O 4 @SiO 2 ‐Ag.…”
Section: Introductionmentioning
confidence: 67%
“…Also, O 2 ‐sensetive functional groups in the primary and secondary alcohols do not change in the oxidant‐free dehydrogenation of alcohols. In recent years, several homogeneous and heterogeneous catalysts have been designed and synthesized for oxidant‐free or acceptor‐free oxidation of alcohols . However, the designing of highly recyclable heterogeneous systems still remains a significant challenge for oxidant‐free dehydrogenation of alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Then, 4 ml of tetraethyl orthosilicate (TEOS) was added dropwisely to the suspension at 40 °C under stirring for 30 min. The pH of this solution was adjusted to 10 by slow addition of NH 3 solution . The reaction mixture was refluxed for 8 hr to allow the base‐catalyzed hydrolysis and condensation of TEOS monomers on the nanoparticle surface go to completion.…”
Section: Methodsmentioning
confidence: 99%